THE INFLUENCE OF DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE PEKANBARU CITY GOVERNMENT DURING THE COVID 19 PANDEMIC - Ratna, Ikhwani; Nasrah, Hidayati (Universitas Riau Kepulauan, 2024)
Since the Covid 19 widespread that hit the world at the conclusion of 2019, it has brought approximately numerous changes in all viewpoints of people's lives. Where specialists are required to proceed to be able to preserve their execution as regular but are constrained by constrained offices and space. This think about points to see the impact of teach and work motivation on worker execution within the Pekanbaru City Government amid the covid 19 widespread. This think about took 100 tests from representatives spread over the Pekanbaru City Government OPD. The survey was prepared utilizing the straight relapse strategy utilizing the SPSS application. Based on the comes about of information processing, it was found from the centrality esteem within the F test, specifically 0.000 which is littler than α = 0.05. The meaning is that it altogether appears that Work Teach, Work Inspiration together have a really genuine impact on Representative Execution in Pekanbaru City Organizations. The comes about of this ponder indicate that worker teach and representative execution at Pekanbaru City Goverment amid the covid 19 widespread are within the great category and have a noteworthy impact on representative execution at Pekanbaru City Goverment. The comes about of this consider are in understanding with the hypothesis put forward which states that work teach and inspiration have an impact on worker execution.